Fracture Toughness and Crack Resistance of Steam Pipeline Steel in Initial and Used States - Zrilic, M.; Burzic, Z.; Cvijovic, Z. (Проблемы прочности, 2004)
Premature fracture of steam pipelines from 14MoV6 3 steel designed for 1000,000 h service life at 540°C has been studied. Test specimens are manufactured from steel in the initial state and after 117 h of operation. Application of the local approach to fracture and the metallographic analysis, in addition to classical methods (tensile, crack resistance, and fatigue strength tests), provided a more precise evaluation of steel properties degradation due to elevated temperatures and stresses. Urgency of further development of the local approach to predicting material fracture after long-term operation at high temperatures has been substantiated.